Biochar Immobilizes and Degrades 2, 4, 6‐Trichlorophenol in Soils. (18th April 2019) - Cui, Liqiang; Yin, Chuntao; Chen, Tianming; Quan, Guixiang; Ippolito, James A.; Liu, Benzhi; Yan, Jinlong; Hussain, Qaiser
Abstract: Soil contamination by chlorophenol compounds, such as 2, 4, 6‐trichlorophenol (2, 4, 6‐TCP), is of great concern because they are environmentally persistent, are difficult to degrade, and can lead to cancer. Thus, means of degrading these compounds in situ are desperately needed. Biochar was investigated as a material to sequester, reduce downward transport, and aid in soil 2, 4, 6‐TCP degradation. In 2 column studies, wheat straw ( Triticum aestivum L.)–derived biochar (pyrolyzed at 450 °C) application to soil (up to 5% by wt) improved soil water and soil organic carbon content. Biochar reduced 2, 4, 6‐TCP downward transport, likely attributable to improved soil water mobility and retention, allowing 2, 4, 6‐TCP to be more easily transported and sorbed to organic functional groups on biochar, leading to enhanced degradation. The 2, 4, 6‐TCP was rapidly degraded into a combination of benzene derivatives and low‐molecular weight organic compounds in the first 2 mo following biochar application. The present study provides evidence that biochars can be used to improve environmental quality by lessening the downward transport and enhancing the degradation of organochlorine compounds such as 2, 4, 6‐TCP. Environ Toxicol Chem 2019;38:1364–1371. © 2019 SETAC